Bio-formulations for disease management - Mawar, Ritu (Indian Farming, 2018)
Our endeavor to prepare and demonstrate use of bioformulated Fig. 2. Rejuvenation of Khejri (A) Before, and (B) after six months of treatment products of bioagents resulted in considerable success to disseminate a non-chemical, cost effective and easy application strategy for managing soil-borne plant pathogens of crops grown under rainfed and irrigated conditions in arid region. Resource deficient growers are not able to adopt technologies where lot of water and expensive external inputs are required. Therefore, use this low input sustainable agriculture technology. Use of bioagents does not require any expensive resources; more so, these products are readily available and can be used by farmers just after an initial on-farm training. These products are made available for distribution to the farmers through (ATIC) of the Institute. In the last 10 years, more than 1,000 ha of land was sown with bioagents coated seeds in the region. The process of developing bioformulated product of these bio-pesticides was published by Indian patent site to put these products for commercialization for wider adaptability among growers. 1Senior Scientist, Corresponding authors’ e.